Kadar Alkali Posfatase dan Kalsium Serum pada Kelompok Risiko Osteoporosis - Akhirul Jumaisal; Norma Rotua S; Sholeha Rezekiyah (Jurnal Keperawatan Silampari, 2023)
This study aims to determine differences in the osteoporosis risk group's increase in ALP levels and total serum calcium. This type of research is an observational analytic using a cross-sectional design. The results showed that the ANOVA repeated measures (Bonferroni) test results for ALP levels obtained a P-value > 0.05, and the total serum calcium level examination received ANOVA test results with a P-value > 0.05. In conclusion, ALP levels and total calcium are not associated with osteoporosis risk groups such as age, sex, steroid use, and smoking habits. Keywords: Alkali Phosphatase, Degenerative, Calcium, Osteoporosis